Entrepreneurship and marketing as ways of firm development in the context of the provision of equal socio-economic opportunities - Wierzbiński, Bogdan (Wydawnictwo Uniwersytetu Rzeszowskiego, 2009)
Changing economy in juxtaposition with the local environment as place of people existing, brings many threats in socio-economical live and business development. Entrepreneurship is one of the ways of giving equal opportunities for the locals not only for the poor areas, entrepreneurship and its function innovativeness makes stronger business position in the context of competitiveness on the market place. Marketing has a very significant role in the process of market development, which is making the business stronger by building more value for consumer and by bringing a new dimension to competitive advantage of the business.

Globalna ekonomia w zestawieniu z lokalnym środowiskiem jako miejscem życia spowodowały wiele zagrożeń w życiu społeczno-ekonomicznym całych społeczności. Przedsiębiorczość jest jednym ze sposobów wyrównywania szans lokalnej społeczności w regionach ubogich, innowacyjność jako jej funkcja wpływa na silniejszą pozycję przedsiębiorstwa w kontekście działań konkurencyjnych na rynku. Bardzo istotne znaczenie posiada również marketing w procesie rozwoju rynku, który powoduje wzmocnienie przedsiębiorstwa poprzez budowanie większej wartości dla konsumenta i jest czynnikiem budowania przewag konkurencyjnych przedsiębiorstwa.
Przedsiębiorczość i marketing sposobami rozwoju firmy w kontekście stwarzania równych szans społeczno-gospodarczych